Margins as Methods, Margins as Ethics: A Feminist Framework for Studying Online Alterity. (March 2020) - Clark-Parsons, Rosemary; Lingel, Jessa
Prevailing theories of marginalized media position the work of resistance as beneath or less than the institutions against which resistance works, raising a number of methodological and ethical challenges for research on online alterity. We offer a margins-as-methods approach for studies of social media on the margins, directing critical attention to the theoretical, ethical, and political implications of positioning subsets of social media users as peripheral to an imagined center. Drawing on theories of feminist reflexivity and our own fieldwork experiences, we articulate the margins-as-methods approach through two sets of practices: deconstructing the power politics behind theories of alterity and identifying how these power politics shape every stage of the research process. We conclude by offering guiding questions for researchers to reflect on as they evaluate the methodological and ethical challenges specific to their projects. The margins-as-methods approach and the reflexive questions it raises build accountability for how our research process may reinscribe the very power relationships that we, alongside our interlocutors, work to contest.